Intramuscular Adipose Tissue, Sarcopenia, and Mobility Function in Older Individuals - Robin L. Marcus; Odessa Addison; Leland E. Dibble; K. Bo Foreman; Glen Morrell; Paul LaStayo (Journal of Aging Research)
Objective. Intramuscular adipose tissue (IMAT) and sarcopenia may adversely impact mobility function and physical activity. This study determined the association of locomotor muscle structure and function with mobility function in older adults. Method. 109 older adults with a variety of comorbid disease conditions were examined for thigh muscle composition via MRI, knee extensor strength via isometric dynamometry, and mobility function. The contribution of strength, quadriceps lean tissue, and IMAT to explaining the variability in mobility function was examined using multivariate linear regression models. Results. The predictors as a group contributed 27–45% of the variance in all outcome measures; however, IMAT contributed between 8–15% of the variance in all four mobility variables, while lean explained only 5% variance in only one mobility measure. Conclusions. Thigh IMAT, a newly identified muscle impairment appears to be a potent muscle variable related to the ability of older adults to move about in their community.